2019
DOI: 10.1002/app.47668
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding cavitation erosion resistance of hydrophobic polydimethylsiloxane‐based polyurethane coatings

Abstract: Cavitation erosion will create shock waves and water jets in turbulent flows. These impact pressures will affect the surface, which will lead to crack propagation and severe material degradation. In this study, we have developed hydrophobic polydimethylsiloxane‐based polyurethanes (Si‐PUx) with hydroxypropyl polydimethylsiloxane (H‐PDMS) and polytetramethylene glycol (PTMG) as mixed soft segments and 2,4‐tolylene diisocyanate, 1,4‐butanediol, triethanolamine as hard segments via a polycondensation reaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The polymer molecules located near the jet extend conformationally in the direction perpendicular to the jet's motion, while the chain molecules in the rest of the film are compressed. Xiangnian Qiao [ 24 ] noted that the cavitation resistance of the coating is related to the water resistance, hardness, adhesion strength and dynamic mechanical properties of a coating, and the cavitation resistance of a siloxane-modified polyurethane coating is better than that of a high-strength epoxy resin. Furthermore, several studies have shown that metal substrates and coatings interact with each other under impact.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer molecules located near the jet extend conformationally in the direction perpendicular to the jet's motion, while the chain molecules in the rest of the film are compressed. Xiangnian Qiao [ 24 ] noted that the cavitation resistance of the coating is related to the water resistance, hardness, adhesion strength and dynamic mechanical properties of a coating, and the cavitation resistance of a siloxane-modified polyurethane coating is better than that of a high-strength epoxy resin. Furthermore, several studies have shown that metal substrates and coatings interact with each other under impact.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The corrosion resistance of polyurethane coatings on anodised magnesium substrates for aerospace applications were reported by Jothi et al [23] Polyurethane coating functionalised with hydroxypropylpolydimethyl siloxane was found to be an effective anti-cavitation coating for underwater over current components such as propellers, turbine blades etc. [24] Polyurethanes inherently do not possess self-healing properties but it can be made so by either chemical interactions or by supramolecular interactions. [25,26] Self-healing by reversible Diels-Alder reactions is the most popular method.…”
Section: Introductionmentioning
confidence: 99%
“…Alberto et al 32 tested PU resin films reinforced with few-layered graphene (FLG) nanoparticles and observed an improvement of over 100% in the abrasion resistance, a 25% increase in the coefficient of static friction and a 200% increase in the coefficient of dynamic friction. Qiao et al 33 developed hydrophobic polydimethylsiloxane-based PUs (Si-PUx) with hydroxypropyl polydimethylsiloxane (H-PDMS). They showed that the cavitation erosion resistance of Si-PUx coatings improved with an increase in the H-PDMS content.…”
Section: Introductionmentioning
confidence: 99%